A sacola dos direitos humanos: uma proposta de ensino produtivo de gramática a partir do ECA - Bairral, Fernanda Quaranta Lobão (2023)
Human Rights appear as a transversal theme in the main documents guiding Brazilian education, however, there is still a lack of approach in textbooks adopted by public schools. Aiming to stimulate civic practices in Portuguese language classes in basic education, the present work takes as its object the Statute of the Child and the Adolescent, which becomes a support for the exploration of grammatical resources for the construction of meanings, with the development of linguistic analysis in three module activities, namely:, 1) verbal valences and thematic roles; 2) concrete and abstract names; and 3) deontic and epistemic modal auxiliaries, configuring the product The Bag of Human Rights. In module 1, assuming the syntactic-semantic perspective of thematic roles, the activities developed showed that students have difficulty using triple-valence verbs in writing, giving preference to the use of object and beneficiary arguments, nullifying the place of the agent. In module 2, assuming the conception of a noun as “inhabitant of a syntactic house”, an activity was developed to reflect on the noun and adjective categories, which “share a large number of morphic features and which are brought together in the grammatical tradition under the designation name, still maintained today in a nominal phrase” (CASTILHO, 2010, p. 455). And, in module 3, to contribute to citizen emancipation, the use of modalizing auxiliary verbs in Statute of the Child and the Adolescent was explored. This set of modular activities was developed and partially applied to a 9th grade group at the Centro de Excelência Santos Dumont, a school institution located in Aracaju/SE. The objective of the pedagogical product is to support the activities of identifying the characteristics of the document, analyzing its structure, as well as encouraging the exercise of full citizenship, as young people begin to identify themselves as a group and, therefore, understand that have rights and duties in society. The teaching resource contemplates the three steps to achieve a successful result: the initial problematization, the organization of knowledge and the application of knowledge. With this product, we seek to use Portuguese language classes as a space for citizenship training, by resolving the obstacles that prevent the understanding of legal texts, such as the Statute of the Child and the Adolescent, through a contextualized grammar perspective.